Artificial Intelligent Based Damping Controller Optimization for the Multi-Machine Power System: A Review - Hannan M.A.; Islam N.N.; Mohamed A.; Lipu M.S.H.; Ker P.J.; Rashid M.M.; Shareef H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Controllers; Damping; Electric power systems; Flexible AC transmission systems; Linear programming; Optimization; Oscillators (electronic); Rotors; System stability; Damping controllers; Flexible alternating current transmission systems; Objective functions; oscillations; Power system stability; Power system stabilizer (PSS); Stability analysis; Electric power system control